Regional specific effect of saturated vs unsaturated fat on leptin receptor signalling in mice brain areas regulating feeding. (10th January 2023) - Fernández-Felipe, Jesús; López, Lucía L.; Cano, Victoria; Sánchez-Hita, Enrique; Belén Sanz, A.; Chowen, Julie A.; Del Olmo, Nuria; Ruiz-Gayo, Mariano; Merino, Beatriz
Graphical abstract: Highlights: The expression of leptin receptors (LepR) in the hippocampus (HIP) and prefrontal cortex (PFC) is not modified by the intake of high-fat diets. Diets enriched in unsaturated fat (UOLF), but not those enriched in saturated fat (SOLF), impair LepR signalling trough Akt and AMPK. UOLF increases SOCS3 levels specifically in the PFC. UOLF are more deleterious for LepR signalling than SOLF. Abstract: Leptin receptors (LepR) are expressed in brain areas controlling food intake homeostasis, such as the hypothalamus, the hippocampus and the prefrontal cortex. In a previous study we reported that long-term intake of saturated and monounsaturated fat alters hypothalamic LepR signalling. The current study aims at investigating the effect of foods high in either saturated (SOLF) or monounsaturated fat (UOLF) on LepR functionality in the hippocampus and the prefrontal cortex. Male mice were placed on SOLF/UOLF (eight weeks), then treated with recombinant murine leptin (1 mg/kg). After 60 min, brain regions were dissected and processed for western blot of phosphorylated STAT3 (pSTAT3), Akt (pAkt) and AMPK (pAMPK). Levels of SOCS3 were also quantified. SOLF itself increased basal levels of pSTAT3, while UOLF impaired leptin-induced phosphorylation of both Akt and AMPK. SOCS3 levels were specifically increased by UOLF within the prefrontal cortex. Our results show that SOLF and UOLF differently affect LepR signalling within the hippocampus and the prefrontal cortex, which points to the complex effect of saturated and unsaturated fat on brain function, particularly in areas regulating food intake.